2014
DOI: 10.1186/1743-422x-11-157
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Coxsackievirus A6 in hand-foot-mouth disease in Guangzhou, 2010-2012

Abstract: BackgroundHand, foot and mouth disease (HFMD) is usually caused by Enterovirus 71(EV71), and Coxsackievirus A16 (CV-A16) in Guangzhou, the biggest city of South China. However, Coxsackievirus A6 (CV-A6) were observed increased dramatically from 2010–2012.MethodsIn order to understand and to describe the epidemiologic and genetic characteristics of CV-A6, specimens of 5482 suspected HFMD cases were collected and examined by real-time fluorescence PCR. All samples positive for enteroviruses were analyzed by desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 22 publications
5
57
0
Order By: Relevance
“…Indeed, and in agreement with previous studies [12], nearly half of the severe HFMD cases observed in Wenzhou were due to EV-A71, while infections by other enteroviruses often had a mild manifestation. We also confirmed the atypical clinical presentation (more widespread rash, larger blisters and subsequent skin peeling and/or nail shedding) associated with CV-A6 infection [30][31][32][33][34][38][39][40][41][42][43][44][45], and which also affected younger children than EV-A71.…”
Section: Characteristicsupporting
confidence: 79%
See 1 more Smart Citation
“…Indeed, and in agreement with previous studies [12], nearly half of the severe HFMD cases observed in Wenzhou were due to EV-A71, while infections by other enteroviruses often had a mild manifestation. We also confirmed the atypical clinical presentation (more widespread rash, larger blisters and subsequent skin peeling and/or nail shedding) associated with CV-A6 infection [30][31][32][33][34][38][39][40][41][42][43][44][45], and which also affected younger children than EV-A71.…”
Section: Characteristicsupporting
confidence: 79%
“…Our data indicates that most of HFMD cases in Wenzhou were caused by CV-A6. Given the presence of CV-A6 in other parts of China [18,20,38] and abroad [30][31][32][33][34][39][40][41][42][43][44][45], it is clear that more widespread surveillance is needed to determine its potential to ignite a global pandemic.…”
Section: Characteristicmentioning
confidence: 99%
“…The most prominent symptoms include fever and a variety of skin lesions, such as maculopapular or vesicular eruptions in the oral cavity and on the distal extremities, buttocks and genital [1]. HFMD can be caused by multiple different serotypes of human enteroviruses of which enterovirus 71 and coxsackievirus (CV) A16 are most often associated with major outbreaks of HFMD worldwide [2].…”
Section: Why This Case Is Important?mentioning
confidence: 99%
“…In addition, atypical skin manifestations like widespread mucocutaneous bullous reactions mimicking drug adverse reactions, vesiculobullous erosive eruptions, severe vasculitislike rash, rash similar to eczema herpeticum or chickenpox, or rash resembling primary immunobullous disease have been frequently described (6,7). Severe and rare manifestations such as aseptic meningitis, encephalitis, and epididymitis have been reported among children (8,9). From India, Gopal Krishna et al, during the year 2012 published a small cohort of HFMD cases collected from the southern and eastern parts of the country and more than 90% of the infections were attributed to CV-A16 and CV-A6.…”
mentioning
confidence: 99%